Pengaruh pendidikan keuangan di keluarga dan teman sebaya terhadap financial management behavior siswa - Mufida, Imroatul; Sholikhah, Ni’matush (Jurnal Paradigma Ekonomika, 2022)
This study aims to determine the effect of financial education in family and peers on the financial management behavior of XI IPS class students at SMA Negeri 1 Cerme. This type of research is quantitative research. The sample used was purposive sampling a number of students of class XI IPS at SMA Negeri 1 Cerme, namely 109 students. The data collection technique used is a questionnaire. Testing is done by testing the validity and reliability. The analytical test carried out includes the classical assumption test, the hypothesis test and the coefficient of determination test. The data were processed using IBM Statistics SPSS 25. The results of the research on financial education in family and peers had a positive and significant effect on students' financial management behavior. Financial education in a good family will make students not easily influenced by their peers because children already have a basis in behavior so they can control their financial behavior more.